Penanaman Nilai-Nilai Karakter Melalui Ekstrakurikuler Pramuka di Sekolah Dasar - Mujahidah, Idah; Kiranti , Nandia; Malini , Serli; Mulyana , Agus (Jurnal Multidisiplin Indonesia, 2023)
Character education is a combination of character values ​​that must be instilled in students with the hope that they can be implemented in everyday life both in the school environment and in the community. This character education is not only implemented through classroom learning activities, but can also be implemented through extracurricular activities, one of which is pramua. This research aims to analyze the instillation of character values ​​in scout extracurricular activities. This research is a literature study research, data obtained through various literature from research that has been carried out by previous researchers. The results of this research show that character values ​​can be instilled through scout extracurriculars. Coaches can train students based on the scout code of honor along with various training strategies.